Understanding Analytical Exposition Text Writing with an SFL Approach: A Comparative Analysis of Model Text and Student’s Text - Hermayanti, Wina Dwina; Gunawan, Wawan (Ma'soem University, 2024)
This research aims to explore the ability of eleventh-grade students to create analytical exposition texts based on their generic structure and language features, using a descriptive qualitative research approach. The study focuses on comparing model texts with students' writing to describe the types of Systemic Functional Linguistics (SFL) approaches employed and analyze the transitivity in writing analytical exposition. The participants of this study are eleventh-grade students selected based on a teacher's recommendation. The researcher reports the natural phenomena without applying any treatments that could influence the results. The primary objective is to understand the student’s ability to produce analytical exposition texts without intervention. The data collection involves analyzing sentences in the form of students' analytical exposition text assignments provided by the teacher. The researcher examines the clarity of ideas and evaluates the grammatical and generic structure present in the students' writing. This research utilizes a descriptive qualitative approach to capture and describe the natural phenomenon of students' analytical exposition text writing. The findings contribute to understanding the students' proficiency in creating analytical exposition student texts, as well as identifying areas that require further attention in instructional practices.